Multiple Intellegences of Social Sciences and Linguistics Students Grade X Crossing Biology Interest - Rahmadhani Fitri; Ganda Hijrah Selaras; Rika Andima; Rizki Rahman Putra; Resti Fevria; Indra Hartanto (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2019)
Multiple intelligences are the development of intelligence of the brain or intelligence quotient (IQ), emotional intelligence or emotional quotient (EQ), and spiritual intelligence or Spiritual Quotient (SQ). The intelligence consists of nine levels of intelligence is known as the Multiple Intelligences (MI) which includes: linguistic intelligence, mathematical-logical intelligence, visual spatial intelligence, physical-kinesthetic intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence, naturalist intelligence, and existential lntelligence. This theory shows that there is no human activity that uses only one intelligence, but uses all intelligence that exists in humans. Intelligence is a single talent that students use in situations of solving any problem. Every student has a different intelligence. This is because there are several factors that influence it, namely the hereditary factor, interest factor, formation factor, maturity factor, and freedom factor.This research are descriptive study which aims to reveal the level of MI of social sciences and linguistcs student grade X crossing biology interest at SMAN 1V Koto KampungDalam. Results of the study, it was faund that the most dominant intelligence in social science students is naturalist intelligence. In the linguistics scienscestudents, the most dominant intelligence is existential intelligence.